Hubungan Iklim Sekolah dengan Bullying Victimization pada Mahasiswa Ilmu Kesehatan di Sumatera Barat - Alhidaya, Julian Putri; Yasmin, Maya (AHKAM, 2025)
School climate is a crucial factor in creating a safe and supportive learning environment for students, particularly in preventing various social issues such as bullying victimization. Bullying victimization refers to an individual’s experience of being targeted by bullying within an educational context, including verbal, physical, and social exclusion forms. This study aims to analyze the relationship between school climate and bullying victimization among health science students in Sumatera Barat. A quantitative approach was employed, involving 344 students selected through cluster sampling. The research instruments were developed by the authors, with school climate measured based on the theory of Aldridge and Ala’I (2013) and bullying victimization based on the framework of Smith et al. (1999). Data were analyzed using Pearson correlation, which revealed a significant negative relationship between school climate and bullying victimization (r = -0.939, p < 0.05). These findings indicate that the more positive students' perceptions of the school climate, the lower the level of bullying they experience. Conversely, a negative school climate tends to increase the risk of bullying within higher education settings. The results underscore the importance of institutional efforts in fostering a healthy school climate as a preventive strategy against bullying among university students.